Я вернусь...: [роман] / Эльчин Сафарли - Сафарли Эльчин (АСТ, 2010)
Экземпляры: ф.15 (20230413) / Инвентарный номер: 56369 / Цена: 160.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: С 12 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-44